Dialog med avtorjem in naslovnikom v pridigi Primoža Trubarja - Bizjak Končar, Aleksandra (Jezik in slovstvo, 2019)
Trubar's sermon Sermo de vocabulo fidei in the Cathesismus from 1550 (1935: 202-243) has an important position in Slovenian literary history, as it is the first preserved sermon created by a Slovenian author explicitly labelled as a sermon. The article examines the dialogic aspects of Trubar's sermon by making explicit the relations between the author and his audience. By applying Cloran's method of rhetorical analysis (1994), it is possible to identify the typical interactional rhetorical units referring to the participants of the text: the author and the listener. The focus of the analysis of Trubar's sermon is a detailed account of rhetorical units that signify (1) the author's and listener's textual presence, and (2) the author's engagement of the listener. With these linguistic devices, a strong interactional link is created between Trubar/the preacher and the silent audience.
Keywords: avtor; dialog; naslovnik; pridige; retorične enote; sistemsko-funkcijska teorija jezika; slovenska književnost; Trubar, Primož: Sermo de vocabulo fidei; Trubarjeva pridiga